Peningkatan Pengetahuan Ibu Hamil tentang ANC di Era New Normal - Farida Yuliani; Erfiani Mail; Fitria Edni Wari (LPPM Akbid Harapan Ibu Pekalongan, 2021)
This community service activity aims to increase the knowledge of pregnant women about Ante Natal Care (ANC) in the new normal era in Gayaman Village, Mojoanyar District. The method used is a lecture and the measuring instrument used is a questionnaire. The material given to pregnant women is about Ante Natal Care (ANC). This activity was attended by 31 pregnant women in Gayaman Village, Mojoanyar District in March 2021–July 2021. The results obtained were 100% of the participants had good knowledge about knowledge of pregnant women about ANC during this pandemic. Pregnant women and health workers should strictly maintain health protocols during ANC checks during this pandemic to avoid the dangers of covid 19.